Das Konzept des Analysisunterrichts von Professor Igor Kluvánek – einige Ergebnisse der qualitativen Forschung - Gunčaga, Ján (Teaching Mathematics and Computer Science, 2007)
A renowned Slovak mathematician Professor Igor Kluvanek (1931-1993) during his affiliation with the University of Adelaide in Australia (1968-1990) has worked out a unique course of mathematical analysis for future high school teachers of mathematics. The course has been tested in its conceptual form but, as a whole, it still awaits its publication in the form of a monograph. Along these lines, our aim is to present the way he has introduced some key notions of differential calculus and to discuss its advantages. Central is the continuity of a function via which the limit and the derivative of a function at a point is defined.